Implementation and Application of Functional Languages 23rd International Symposium, IFL 2011, Lawrence, KS, USA, October 3-5, 2011, Revised Selected Papers - Gill, Andy.; Hage, Jurriaan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 23rd International Symposium on Implementation and Application of Functional Languages, IFL 2011, held in Lawrence, Kansas, USA, in October 2011. The 11 revised full papers presented were carefully reviewed and selected from 33 submissions. The papers by researchers and practitioners who are actively engaged in the implementation and the use of functional and function based programming languages describe practical and theoretical work as well as applications and tools. They discuss new ideas and concepts, as well as work in progress and results.
Functional Instrumentation of ActionScript Programs with Asil -- Fairness for Transactional Events -- Implementing a High-Level Distributed-Memory Parallel Haskell in Haskell -- Challenges for a Trace-Based Just-In-Time Compiler for Haskell -- Lazy Generation of Canonical Test Programs -- Generic Monadic Constructs for Embedded Languages -- From Stack Traces to Lazy Rewriting Sequences -- Model Based Testing with Logical Properties versus State Machines -- Property-Based Testing and Verification: A Catalog of Classroom Examples -- Describing and Optimising Reversible Logic Using a Functional Language -- Hardware Design with Generalized Arrows.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Software Engineering; Mathematical Logic and Formal Languages; Programming Techniques